Electromagnetic-triboelectric energy harvester based on vibration-to-rotation conversion for human motion energy exploitation. (1st January 2023) - Bai, Shanming; Cui, Juan; Zheng, Yongqiu; Li, Gang; Liu, Tingshan; Liu, Yabing; Hao, Congcong; Xue, Chenyang
Graphical abstract: Highlights: Electromagnetic-triboelectric hybrid energy harvester based on vibration-to-rotation conversion is proposed. Rotation and reciprocating vibration energy are simultaneously captured and converted to improve the efficiency of irregular human motion harvesting. Stable and high active power output satisfies self-power requirements of wearables and wireless sensor electronics. Abstract: To overcome the frequent replacement and charging of chemical batteries, human motion has become a promising energy source for portable electronic devices and wireless monitoring equipment. Although various energy harvesters for the conversion of human energy into electrical energy have been investigated, the output performance of existing harvesters is too low and irregular to provide sustained power to electronic devices. This paper proposes a high-efficiency electromagnetic-triboelectric hybrid energy harvester (ET-HEH) based on vibration-to-rotation conversion. The proposed harvester comprises a rotational electromagnetic generator (REMG), motion transmission mechanism, and reciprocating vibration triboelectric nanogenerator (VTENG). Rotational and vibrational energy can be transmitted among these components and harvested synchronously to enhance the output. The experimental results reveal that the energy conversion efficiency of ET-HEH can reach more than 70 % under multiple vibration frequencies. The proposed harvester has higher output compared with traditional reciprocating vibration energy harvesters. The active power output of the harvester after rectification is stably maintained at approximately 300 mW during jogging, exceeds 800 mW during sprinting, and can continuously charge a smart band with a rated power of 400 mW. This study demonstrates a new mechanism for realizing vibration-to-rotation conversion and provides a practical approach toward the harvesting of human motion energy with high-efficiency.